Plasmacytoid dendritic cells regulate colitis-associated tumorigenesis by controlling myeloid-derived suppressor cell infiltration - Ko, Hyun Jeong; Hong, Eun Hye; Cho, Jaewon; Ahn, Jae hee; Kwon, Bo Eun; Kweon, Mi Na; Seo, Sang Uk; Yoon, Byung Il; Chang, Sun Young (Cancer Letters, 2020)
Toll-like receptor (TLR)3 and TLR7 are important for stimulating plasmacytoid dendritic cells (pDCs), which secrete type I interferon. Mice deficient for TLR3 and TLR7 (TLR3−/−TLR7−/−) reportedly exhibit deteriorated colitis because of impaired pDCs. However, the role of pDCs in tumorigenesis-associated inflammation progression has not been studied. We treated wild-type or TLR3−/−TLR7−/− mice with dextran sulfate sodium (DSS) and/or azoxymethane (AOM) and examined colon mucosa, measured body weight and colon length of mice, and examined pDC and myeloid-derived suppressor cell (MDSC) accumulation. Further, we depleted pDCs in AOM/DSS-treated wild-type mice by treating them with anti-PDCA-1 antibodies. We found that MDSCs significantly increased, while pDCs decreased in TLR3−/−TLR7−/− mice. Moreover, TLR3−/−TLR7−/− mice developed colitis-associated colon cancer following AOM/DSS treatment. Additionally, we showed that a defect in TLR7 of pDCs is responsible for the aggravation of colitis-associated colon cancer. Further, we showed that TLR7 ligand mitigates colitis-associated colon cancer. Collectively, our results demonstrate that gut pDCs play a crucial role in reducing colorectal cancer development via the regulation of infiltrating MDSCs.
Keywords: Animals; Azoxymethane; Body Weight; Cell Line, Tumor; Colitis; Colonic Neoplasms; Dendritic Cells; Dextran Sulfate; Disease Models, Animal; Disease Progression; Female; Gene Knockout Techniques; Membrane Glycoproteins; Mice; Myeloid-Derived Suppressor Cells; Signal Transduction; Toll-Like Receptor 3; Toll-Like Receptor 7; Colorectal cancer; Myeloid-derived suppressor cell; Plasmacytoid dendritic cell; Toll-like receptor